Implementasi Model Evaluasi CIPP untuk Mewujudkan Pembelajaran Bahasa Arab Holistik dalam Kurikulum Merdeka - Adlya, Fadia Iftakhul; Salsabila, Alfana; Baity, Anggi (Program Studi Pendidikan Bahasa Arab, 2025)
The implementation of the Merdeka Curriculum at the islamic education institution, including Islamic elementary schools, requires a comprehensive evaluation system to ensure the success of both the learning process and its outcomes. MI Al-Azhar, as one of the institutions implementing this curriculum, faces various challenges, particularly in Arabic language learning. This study aims to describe the implementation of the CIPP evaluation model (Context, Input, Process, Product) in Arabic language learning and to identify the challenges encountered in its application at MI Al-Azhar Kediri. A descriptive qualitative approach was employed, with data collected through observation, structured interviews, and documentation. The findings indicate that the CIPP model assists teachers and schools in conducting comprehensive evaluations, covering planning, implementation, and learning outcomes. However, its application in practice faces several obstacles, including limited resources, discrepancies between the curriculum and its implementation, and teachers’ limited mastery of digital media. These findings highlight that the CIPP model is an effective approach for evaluating Merdeka Curriculum-based learning in madrasahs, although it requires adequate support in terms of resources and teacher competencies.